Reverse Ordered Sequential Mechanism for Lactoperoxidase with Inhibition by Hydrogen Peroxide - Kellye Cupp-Sutton (MDPI AG, 2021)
Lactoperoxidase (LPO, FeIII in its resting state in the absence of substrates)—an enzyme secreted from human mammary, salivary, and other mucosal glands—catalyzes the oxidation of thiocyanate (SCN−) by hydrogen peroxide (H2O2) to produce hypothiocyanite (OSCN−), which functions as an antimicrobial agent. The accepted catalytic mechanism, called the halogen cycle, comprises a two-electron oxidation of LPO by H2O2 to produce oxoiron(IV) radicals, followed by O-atom transfer to SCN−. However, the mechanism does not explain biphasic kinetics and inhibition by H2O2 at low concentration of reducing substrate, conditions that may be biologically relevant. We propose an ordered sequential mechanism in which the order of substrate binding is reversed, first SCN− and then H2O2. The sequence of substrate binding that is described by the halogen cycle mechanism is actually inhibitory.